PENGARUH LATIHAN PLYOMETRIC TERHADAP KEMAMPUAN TENDANGAN DOLLYO CHAGI ATLET TAEKWONDO SASANA CENDANA FIGHTER KOTA PADANG - Putra, Defin Marsyah; Mariati, Sari; Setiawan, Yogi; Sari, Desi Purnama; Putra, Yogi Arnaldo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem addressed in this study is the still low level of Dollyo Chagi kicking ability among Taekwondo athletes at Cendana Fighter Taekwondo Club, Padang City. The purpose of this study was to determine whether plyometric training has an effect on improving the Dollyo Chagi kicking ability of Taekwondo athletes at Cendana Fighter Taekwondo Club, Padang City. This study employed a quasi-experimental research design. The research was conducted from May to June 2026 at Cendana Fighter Taekwondo Club, Padang City. The population consisted of all 12 Taekwondo athletes at Cendana Fighter Taekwondo Club, Padang City. The sampling technique used was total sampling; therefore, the sample comprised all 12 athletes. The research instrument was a Dollyo Chagi kicking ability test. Data were analyzed using the statistical mean difference test (t-test). The results of the study showed that plyometric training had an effect on the Dollyo Chagi kicking ability of Taekwondo athletes at Cendana Fighter Taekwondo Club, Padang City, with a calculated t-value (t-count) of 2.04 and a t-table value of 1.79 (2.04 > 1.79).